Nursing students collaborating to develop multiple-choice exam revision questions: A student engagement study - Craft, Judy A.; Christensen, Martin; Shaw, Natasha; Bakon, Shannon (Nurse education today, 2017)
Nursing students find bioscience subjects challenging. Bioscience exams pose particular concerns for these students, which may lead to students adopting a surface-approach to learning. To promote student collective understanding of bioscience, improve their confidence for the final exam, and improve deeper understanding of bioscience. In order to address exam anxiety, and improve student understanding of content, this student engagement project involved nursing students collaborating in small groups to develop multiple-choice questions and answers, which became available to the entire student cohort. This study was conducted at two campuses of an Australian university, within a first year bioscience subject as part of the undergraduate nursing programme. All students enrolled in the subject were encouraged to attend face-to-face workshops, and collaborate in revision question writing. Online anonymous questionnaires were used to invite student feedback on this initiative; 79 respondents completed this feedback. Students collaborated in groups to write revision questions as part of in-class activities. These questions were made available on the student online learning site for revision. An online feedback survey was deployed at the conclusion of all workshops for this subject, with questions rated using a Likert scale. Participants indicated that they enjoyed the opportunity to collaborate in this activity, and almost all of these respondents used these questions in their exam preparation. There was strong agreement that this activity improved their confidence for the final exam. Importantly, almost two-thirds of respondents agreed that writing questions improved their understanding of content, and assisted in their active reflection of content. Overall, this initiative revealed various potential benefits for the students, including promoting bioscience understanding and confidence. This may improve their long-term understanding of bioscience for nursing practice, as registered nurses' bioscience knowledge can impact on patient outcomes. •Nursing students find bioscience challenging, and may resort to surface learning.•Registered nurses recognise the importance of bioscience understanding.•First year nursing students collaborated to generate exam revision questions.•Student-generated revision questions were useful for student's exam preparation.•This increased student bioscience confidence, content understanding and reflection.